Preparation method of hollow ATZ ceramic ball for bearing and hollow grouting plaster mold
Through the preparation method of hollow ATZ ceramic balls, the problem of high centrifugal force caused by high density of ceramic bearings is solved, and the preparation of low-density and high-hardness ceramic balls is realized, which improves the wear resistance and stability of the bearings and broadens its application range.
Patent Information
- Application Number
- CN202510251843.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-05
AI Technical Summary
The existing ceramic bearing material has high density, which leads to a large centrifugal force when rotating at high speed, limiting its feasibility in high speed environments.
The preparation method of hollow ATZ ceramic balls is adopted to form ceramic balls through hollow grouting gypsum molds to achieve low density and high hardness of ceramic balls, reducing the inertia and weight of bearing balls.
It improves the wear resistance, stability and overall performance of ceramic bearings, broadens its application range in high speed and harsh environments, and reduces the production cost.
Smart Images

Figure CN119748602A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of structural ceramic bearings, and in particular to a preparation method of a hollow ATZ ceramic ball for a bearing and a hollow grouting gypsum mold. Background Art
[0002] With the rapid development of industrial technology, the requirements for bearings are getting higher and higher, which are specifically reflected in: precision requirements in size, high speed requirements, high temperature requirements, high vacuum, corrosion resistance and other more demanding working conditions are also increasing. Some performances of bearings made of steel materials can no longer be met. A large number of tests have proved that the precision bearing ball working in a high-speed environment is the weakest part of the bearing. About 60% to 70% of high-speed bearing failures are caused by fatigue damage of steel balls to varying degrees. Research results at home and abroad show that the use of structural ceramics to manufacture spheres or other bearing parts can significantly improve the performance and life of high-speed bearings.
[0003] In the fields of aerospace, navigation, nuclear industry, petroleum, chemical industry, textile industry, machinery, metallurgy, electricity, new energy, food, locomotive, subway, high-speed machine tools, etc., bearings are required to work under special working conditions such as high temperature, high speed, deep cold, flammable, explosive, strong corrosion, vacuum, electrical insulation, non-magnetic, dry friction, easy to rust, etc., and the indispensable replacement role of ceramic bearings is gradually being recognized by people. With the continuous advancement of processing technology and the increasing improvement of process level, the cost of ceramic bearings has been continuously reduced. It has been gradually promoted to various industrial fields of the national economy from being only used in a small range in some high, precise and advanced fields in the past. Through the test of batch and long-term use in different industries. Many successful cases have realized the advantages of maintenance-free, long life, high stability and low cost brought by ceramic bearing balls and all-ceramic bearings. Ceramic bearings and ceramic bearing balls have moved from the research and trial production stage to the stage of mass production, and the wave of large-scale application has come.
[0004] The existing ceramic bearing materials commonly used are zirconium oxide and silicon nitride; Characteristics of silicon nitride ceramics: The density of silicon nitride ceramics is only 3.2-3.2g / cm3, and the high temperature operating temperature reaches 1000℃. It has low-temperature insulation, is non-magnetic, and has a hardness of more than HV1 1600. It has good low-temperature insulation and has strong conductivity when the temperature exceeds 1000℃. Due to the high preparation cost of silicon nitride ceramic bearings, the equipment used in the preparation of powders requires high temperature and high pressure to isolate the air, and the later ceramic molding and sintering also requires relatively harsh conditions. Finally, the processing cost of high-hardness ceramics is also high, so its application and promotion scope is subject to certain restrictions.
[0005] Characteristics of zirconia ceramics: The density of zirconia bearing beads is 6.08g / cm 3, the operating temperature is 800-900℃, with strong corrosion resistance; high bending strength and toughness. Compared with silicon nitride materials, the preparation process is relatively simple, the cost of the blank is low, and it is easy to apply in the market. At the same time, the toughness of zirconium oxide is higher than that of silicon nitride, which is conducive to the stable use of bearings. In addition, the thermal expansion coefficient of zirconium oxide is close to that of steel, which improves its stability in mechanical structures. However, the high density of zirconium oxide ceramics leads to a large centrifugal force on the bearing, which is not conducive to high-speed rotation and limits its application field.
[0006] Characteristics of zirconia ceramics (ATZ ceramics) with 20%A mass fraction of alumina added, density 5.4-5g / cm 3 The flexural strength is close to that of zirconia ceramics, the toughness and hardness are higher than those of zirconia ceramics, and the hydrothermal aging resistance is also better.
[0007] The density of zirconium oxide is 6.08, which is much higher than that of silicon nitride ceramics, which is 3.2. This means that when it is used as a rolling element, the centrifugal force generated by the rotating body during the rotation of the bearing increases, and the weight of the bearing itself increases, which limits its application in high-speed environments. The present invention is to develop a larger-sized hollow ATZ ceramic precision bead for bearings, which has high hardness, low density, and excellent mechanical properties in all aspects. It is inexpensive and can be used in bearings in higher speed and harsher environments. Summary of the invention
[0008] The purpose of the present invention is to provide a preparation method of hollow ATZ ceramic balls for bearings and a hollow grouting gypsum mold. The hollow ceramic balls made of ATZ material have a lower density than silicon nitride and do not require the same stringent preparation conditions as silicon nitride. They only need to be sintered at normal pressure, and the sintering temperature is much lower than that of silicon nitride balls and is close to that of zirconia ceramics. The hollow ceramic balls made of ATZ material have a higher hardness than zirconia ceramic beads, a slightly higher strength than zirconia ceramic beads, and good roundness, which improves the wear resistance and stability of ceramic bearings, thereby improving the overall performance of ceramic bearings.
[0009] The present invention adopts the following technical solution: A method for preparing a hollow ATZ ceramic ball for a bearing comprises the following steps: S1. Determine the shrinkage ratio according to the empirical formula based on the size of the hollow ATZ ceramic ball, and calculate the spherical cavity size of the water-absorbing gypsum mold and the solid content of the ATZ slurry to be configured according to the shrinkage empirical formula; S2. Take ATZ powder and mix the materials according to the solid content of the ATZ slurry to be configured according to the empirical formula, and grind to obtain ATZ slurry with uniform fineness; prepare a hollow spherical gypsum mold, assemble it according to the method for using the gypsum mold, take the ATZ slurry with uniform fineness of the volume of the spherical cavity in the gypsum mold, add it into the cavity of the gypsum mold through the slurry filling port, and seal the gypsum mold; S3, fix the sealed gypsum mold in a planetary ball mill, and then rotate it at high speed for 2-3 hours. The rotation of the planetary ball mill allows the slurry to evenly contact the inner surface of the gypsum mold. As the rotation time of the planetary ball mill increases, the gypsum mold continuously absorbs moisture. Finally, the ATZ slurry with uniform fineness inside the gypsum mold is completely and evenly adhered to the wall and solidified to form a hollow ATZ ceramic green ball; S4, removing the gypsum mold with the hollow ATZ ceramic green ball and drying it, because the two materials shrink differently and produce delamination, the hollow ATZ ceramic green ball falls off, and then disassembling the gypsum mold according to the disassembly method of the gypsum mold, and taking out the hollow ATZ ceramic green ball; S5. Take one of the hollow ATZ ceramic green balls from the same batch and knock it open to observe whether there is any slurry lump that has not been completely absorbed by the gypsum mold; if not, it is judged to be qualified; S6. The qualified batch of hollow ATZ ceramic green balls are sintered according to a certain normal pressure air atmosphere sintering system, and then polished according to a certain polishing method after sintering. The polished hollow ATZ ceramic green balls are sorted according to a certain sorting method to obtain the final qualified hollow ATZ ceramic balls for bearings.
[0010] Preferably, the empirical formula in step S1 is: Formula (1) Formula (2) Formula (3) Formula (4) ρ 空 : Density of hollow ATZ ceramic ball, unit: g / cm 3 ; The smaller the density, the better, but D 空 / D 外 The value should be less than 0.77 to ensure that the wall thickness is thick enough to maintain its mechanical properties under high-speed operation.
[0011] ρ 实 : Theoretical or optimal sintering density of ATZ ceramic material, unit: g / cm 3 For example, 20wt% ATZ generally sintered to a density of 5.45-5.5g / cm3 ; ρ 生坯层 : Density of the dense part of the hollow ATZ ceramic green ball after demolding after slip injection molding, unit: g / cm 3 ; This data can be obtained through a small experiment. When the particle size of the injection molding slurry and the proportion of organic solute added are relatively stable, it is a constant, unit: g / cm 3 ; ρ 水 : Density of pure water, unit: g / cm 3 ; D 外 : The outer diameter of the qualified hollow ATZ ceramic ball after final polishing, in mm; D 外生坯 : The outer diameter of the hollow ATZ ceramic green ball, that is, the inner diameter of the cavity of the gypsum mold, in mm; D 空生坯 : Hollow cavity diameter of hollow ATZ ceramic green ball, unit: mm; D 空 : The inner diameter of the qualified hollow ATZ ceramic ball after final polishing, in mm; K1: The shrinkage ratio of the hollow ATZ ceramic green ball after sintering, which is the ratio of the ball diameter after sintering to the diameter before sintering. This coefficient can be simply obtained through experiments and is a constant value if the slurry particle size and the solute formula therein are relatively stable; K2: The moisture content of hollow ATZ ceramic green balls is to grind a hollow green ball into powder and then put it in a moisture meter to measure the moisture content. If the slurry particle size and the solute formula are relatively stable, this data can also be obtained simply through experiments. K3: Polishing compensation coefficient, unit: mm, which is the diameter of the hollow ATZ ceramic ball after sintering minus the diameter of the qualified hollow ATZ ceramic ball after polishing; SC: solid content of ATZ slurry to be prepared; The above four empirical formulas and related empirical constants can be used to calculate the solid content of the ATZ slurry and the spherical cavity size of the gypsum mold required for grouting of the hollow ATZ ceramic ball to be designed.
[0012] Preferably, in step S2, the proportion of 3Y zirconium oxide in the ATZ powder is 80 parts by mass, and the proportion of aluminum oxide is 20 parts by mass.
[0013] Preferably, in step S2, 0.3-0.5% of a dispersion stabilizer is added to the ATZ slurry being ground, and the dispersion stabilizer is CE64 or polyacrylic acid.
[0014] Preferably, the rotation speed of the planetary ball mill is 300-400r / min.
[0015] Preferably, in step S4, the drying temperature is between 30-40° C. and the drying time is 3-6 hours.
[0016] Preferably, in step S6, the normal pressure air atmosphere sintering system is: the heating rate at 0-120°C is 1.5-2°C / min, the heating rate at 120-350°C is 0.4-0.6°C / min, the heating rate at 350-650°C is 0.3-0.5°C / min, the temperature is kept at 650-650°C for 120min, the heating rate at 650-1450°C is 1.0-1.2°C / min, the temperature is kept at 1450°C for 180min, and the cooling rate at 1450-1000°C is 1.5-2.0°C / min.
[0017] Preferably, in step S6, the polishing method is: firstly perform rough polishing: add 60-70wt% of hollow ATZ beads, 20-25wt% of pure water, 4-5wt% of 20-50µm white corundum particles, and 0.5wt% of polyacrylic acid dispersant in a vertical sand mill; then perform fine polishing: add 50-60wt% of the hollow ATZ beads after rough polishing, 25-30wt% of pure water, and 6-8wt% of 1-5µm alumina powder in a vertical sand mill.
[0018] Preferably, in step S6, a certain sorting method is: first, use a roughness detector to sort out hollow ATZ ceramic balls with a roughness less than 0.05 μm as roughness qualified products; then use a laser particle size analyzer to test the roundness of each hollow ATZ ceramic ball, and use a roundness greater than or equal to 99.9% as a roundness qualified product; then perform a density test to sort out hollow ATZ ceramic balls with a density less than or equal to 3g / cm3 as qualified products; then perform quality classification, and put hollow ATZ ceramic balls with a mass deviation of less than 0.05g into the same box for storage; then sort the hollow ATZ ceramic balls with a mass difference of less than 0.05g according to size, and finally sort out the hollow ATZ ceramic balls with a diameter error within the design size ±0.05mm as final qualified products.
[0019] A hollow grouting gypsum mold comprises a plug assembly, an upper mold convex assembly, a lower mold concave assembly and a lower mold concave-convex assembly. The upper mold convex assembly is spliced and assembled with the lower mold concave-concave assembly and the lower mold concave-convex assembly. After assembly, a spherical cavity is formed between the upper mold convex assembly, the lower mold concave-concave assembly and the lower mold concave-convex assembly. A slurry filling port is opened on the upper mold convex assembly to connect the spherical cavity, and the plug assembly is sealed on the slurry filling port.
[0020] The beneficial effects of the present invention are: (1) The method of the present invention can obtain ATZ ceramic balls with a specific hollow size, which have the characteristics of lower density than silicon nitride balls, higher hardness than zirconia balls, higher toughness and strength than zirconia balls, and improve the durability of ceramic bearings, etc., which can broaden the application limits of ceramic bearings, and the preparation cost is lower than that of silicon nitride balls; (2) The present invention uses a certain hollow method to further reduce the density of the ATZ ceramic ball, so that without affecting its mechanical properties, the density of the final hollow ATZ ceramic ball is slightly lower than that of silicon nitride, which can improve the durability of the bearing. This is because if the bearing ball is solid, then when running at high speed, the inertia of the bearing ball will be very large, and huge inertial force and impact force will be generated during acceleration and deceleration, which can easily cause damage to the bearing. Therefore, the hollow design of the bearing ball is to reduce the inertia and weight of the bearing, improve the operating efficiency and service life of the bearing, which can also increase the rotation speed of the motor; (3) The larger the bearing radius, the faster the angular velocity, and the larger the mass, the greater the force exerted by the ball on the bearing wall. When the angular velocity and radius are constant, the mass of the bearing ball is proportional to the centrifugal force. The hollow ATZ ceramic ball produced by the present invention has a small mass, a small centrifugal force, a small force between the ball and the bearing wall, and a reduced friction loss of the ball, thereby improving the durability of the bearing. (4) Ceramic balls used in bearings need to have a high degree of roundness and a smooth surface. In addition to achieving hollowness, the roundness of the ball must also be ensured. Slurry injection molding is the best choice. The surface of the blank after molding has fewer defects, and the subsequent polishing surface is easier to smooth. The higher the roundness, the more uniform the rotation force of the bearing, the better the rotation effect, and the improved durability and reliability under high-speed rotation. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the cross section of the hollow ATZ ceramic ball of the present invention; Figure 2 This is a process flow chart of the preparation of hollow ATZ ceramic balls of the present invention; Figure 3 This is a plan view of the inlaid 30 mm hollow ATZ beads prepared in an embodiment of the present invention; Figure 4 It is an overall schematic diagram of the hollow grouting gypsum mold of the present invention; Figure 5 It is a structural schematic diagram of a hollow grouting gypsum mold plug assembly of the present invention; Figure 6 It is a structural schematic diagram of the upper mold convex component of the hollow grouting gypsum mold of the present invention; Figure 7 It is a structural schematic diagram of the concave and concave components of the lower mold of the hollow grouting gypsum mold of the present invention; Figure 8 It is a structural schematic diagram of the concave-convex component of the lower mold of the hollow grouting gypsum mold of the present invention; In the figure: 1. plug assembly, 2. upper mold convex assembly, 3. lower mold concave assembly, 4. lower mold concave-convex assembly, 1-1. spherical inner concave surface, 1-2. convex block, 1-3. cylindrical plugging rod, 2-1. limiting boss, 2-2. hemispherical hollow cavity, 2-3. slurry filling port, 3-1. concave limiting slot one, 3-2. limiting groove, 3-3. one quarter hollow spherical cavity one, 4-1. concave limiting slot two, 4-2. limiting protrusion, 4-3. one quarter hollow spherical cavity two. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is further described in detail below through specific embodiments and in conjunction with the accompanying drawings: Embodiment: To make Figure 1 The bearing shown in the figure uses hollow ATZ ceramic balls. Figure 2 The steps shown are as follows: First, according to the empirical formula, the design of the hollow ATZ ceramic ball with an outer diameter of 30 mm corresponds to D in the empirical formula. 外 =30mm. 20%Al2O3ATZ material setting ρ 实 5.5g / cm 3 , ρ 空 Set to 3.0g / cm 3 , substitute into the empirical formula (1) to get D 空 =D=23.066mm, D 空 / D 外 =0.769<0.77, composite design requirements; according to experience, the polishing compensation coefficient K3 is set to 0.5mm, according to experience, the sintering shrinkage coefficient K1 is set to 0.72, and then the diameter D of the hollow green body is obtained according to the empirical formula (2) 外生坯 =42.361mm, according to the empirical formula (3)D 空生坯 =32.036mm, in the empirical formula (4), ρ is set according to experimental experience 生坯层 3.6g / cm 3 , the ambient temperature is 25℃, take ρ 水 0.99705g / cm 3 According to empirical tests, the moisture content K2 of the hollow green ATZ ball is 0.25. Substituting these parameters into formula (4), the solid content of the ATZ slurry to be configured is obtained as SC=0.619.
[0023] Secondly, mixing and grinding, grouting slurry: according to SC data, ATZ dry powder, pure water and dispersing stabilizer are mixed, and 0.3% dispersing stabilizer is added, and ATZ slurry with uniform fineness is obtained by ball milling. 外生坯 The diameter of the spherical cavity of the water-absorbing gypsum mold is obtained, and accessories are assembled according to the method for using the hollow gypsum mold. A uniform slurry with an amount corresponding to the volume of the spherical cavity of the gypsum mold is added to the cavity of the gypsum mold, and the gypsum mold is assembled and sealed.
[0024] Then, it rotates at high speed in a planetary ball mill: the assembled and sealed gypsum mold is fixed in the planetary ball mill, and then rotated at 500r / min for 2h. The rotation of the planetary ball mill allows the slurry to achieve uniform contact with the inner surface of the hollow gypsum mold. As the rotation time of the planetary ball mill continues, the gypsum mold continues to absorb moisture, and finally the slurry inside the gypsum mold is completely and evenly adhered to the wall and solidified to form a hollow ATZ ceramic green ball.
[0025] Then, dry, dismantle the mold, and take out the hollow ATZ ceramic green ball: remove the gypsum mold of the hollow ATZ ceramic green ball and put it into an oven with a set temperature of 35°C and dry it for 3 hours. Due to the different shrinkage of the two materials, the layered hollow ATZ ceramic green ball will fall off. Then dismantle the mold according to the disassembly method of the gypsum mold and take out the hollow ATZ ceramic green ball.
[0026] Then, check whether the hollow ATZ ceramic green balls from the same batch are qualified: take one of the hollow ATZ ceramic green balls from the same batch, knock it open and observe to confirm whether there are slurry lumps that have not been completely absorbed by the gypsum mold, and whether a spherical cavity is formed; if not, a spherical cavity is formed; then it is judged to be qualified.
[0027] Finally, sintering, polishing and sorting qualified balls: for qualified batches of green hollow ATZ balls, the heating rate is 1.5℃ / min at 0-120℃, 0.6℃ / min at 120-350℃, 0.4℃ / min at 350-650℃, 650-650℃ insulation for 120min, 650-1450℃ heating rate is 1.5℃ / min, 1450℃ insulation for 180min, and the cooling rate is 1.7℃ / min at 1450-1000℃. The sintering was carried out in a normal pressure air atmosphere sintering system; 65 parts by mass of the sintered hollow ATZ ceramic balls were added to a vertical sand mill, and then 30 parts by mass of pure water and 5 parts by mass of white corundum particles with an average particle size of 30 μm were added, and then 0.5 parts by mass of polyacrylic acid was added as an auxiliary agent for rough polishing; the rough polished balls were then finely polished, and the fine polishing conditions were: 55 parts by mass of the hollow ATZ ceramic balls after rough polishing, 30 parts by mass of pure water, 8 parts by mass of 3μm alumina powder were added to the vertical sand mill, and then 0.5 parts by mass of polyacrylic acid was added as an auxiliary agent for rough polishing. .5 parts by mass of polyacrylic acid is used as an auxiliary polishing agent; the hollow ATZ ceramic balls after fine polishing are sorted, firstly sorted according to surface roughness, and the hollow ATZ ceramic balls with a roughness of less than 0.05μm are screened out as qualified roughness products; the hollow ATZ ceramic balls with qualified roughness are then tested for roundness by a laser particle size analyzer, and the hollow ATZ ceramic balls with a sphericity of 99.9% are selected as qualified sphericity products; the selected hollow ATZ ceramic balls are then tested for density, and the hollow ATZ ceramic balls with a density of less than 3g / cm 3 The hollow ATZ ceramic balls with a mass difference of less than 0.05g are sorted out as qualified products: the quality is then sorted, and the hollow ATZ ceramic balls with a mass difference of less than 0.05g are placed in the same box for storage. The hollow ATZ ceramic balls with a mass difference of less than 0.05g are sorted out according to size, and the hollow ATZ ceramic balls with a diameter error of 30±0.05mm are sorted out as the final hollow ATZ ceramic balls for bearings with similar density, quality, size, high roundness and small roughness. The central section mosaic structure of the hollow ATZ ceramic ball is as follows Figure 3 shown.
[0028] like Figure 4 As shown, a hollow grouting gypsum mold includes a plug component 1, an upper mold convex component 2, a lower mold concave component 3 and a lower mold concave-convex component 4. The upper mold convex component 2 is spliced and assembled with the lower mold concave-concave component 3 and the lower mold concave-convex component 4. After assembly, a spherical cavity is formed between the upper mold convex component 2 and the lower mold concave-concave component 3 and the lower mold concave-convex component 4. A slurry filling port 2-3 is opened on the upper mold convex component 2 to connect the spherical cavity, and the plug component 1 is sealed on the slurry filling port 2-3.
[0029] like Figure 5As shown, the plug assembly 1 includes a protrusion 1-2 and a cylindrical plugging rod 1-3. The cylindrical plugging rod 1-3 is used to seal the slurry filling port 2-3. A spherical concave surface 1-1 is provided at the end of the cylindrical plugging rod 1-3, and the spherical concave surface 1-1 is provided in cooperation with the spherical cavity.
[0030] like Figure 6 As shown, a hemispherical hollow cavity 2-2 is arranged at the bottom of the upper mold convex component 2, and a slurry filling port 2-3 is arranged at the upper part, the slurry filling port 2-3 is connected to the hemispherical hollow cavity 2-2, and a circle of limiting bosses 2-1 are arranged at the outer edge of the hemispherical hollow cavity at the bottom of the upper mold convex component 2.
[0031] like Figure 7 As shown, a quarter hollow spherical cavity 3-3 is arranged on the upper right side of the lower mold concave-concave component 3, and a half-circle concave limiting groove 3-1 is arranged on the top of the lower mold concave-concave component 3 and the outer edge of the quarter hollow spherical cavity 3-3. The half-circle concave limiting groove 3-1 corresponds to the engaging connection limiting boss 2-1, and a limiting groove 3-2 is arranged on the right side surface of the lower mold concave-concave component 3.
[0032] like Figure 8 As shown, a quarter hollow spherical cavity 2 4-3 is arranged on the upper left side of the lower mold concave-convex component 4, and a half-circle concave limiting groove 2 4-1 is arranged on the top of the lower mold concave-convex component 4 at the outer edge of the quarter hollow spherical cavity 2 4-3, and the half-circle concave limiting groove 2 4-1 corresponds to the matching snap-fit connection limiting boss 2-1, and a limiting protrusion 4-2 is arranged on the left side surface of the lower mold concave-convex component 4, and the limiting protrusion 4-2 corresponds to the matching snap-fit connection limiting groove 3-2.
[0033] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.
Claims
1. A method for preparing a hollow ATZ ceramic ball for a bearing, characterized in that: It includes the following steps: S1. Determine the shrinkage ratio according to the empirical formula based on the size of the hollow ATZ ceramic ball, and calculate the spherical cavity size of the water-absorbing gypsum mold and the solid content of the ATZ slurry to be configured according to the shrinkage empirical formula; S2, taking ATZ powder and proportioning the materials according to the solid content of the ATZ slurry to be prepared according to the empirical formula, and grinding to obtain ATZ slurry of uniform fineness; Prepare a hollow spherical plaster mold, assemble it according to the method of using the plaster mold, take an amount of ATZ slurry with uniform fineness corresponding to the volume of the spherical cavity in the plaster mold, add it into the cavity of the plaster mold through the slurry filling port, and seal the plaster mold; S3, fix the sealed gypsum mold in a planetary ball mill, and then rotate it at high speed for 2-3 hours. The rotation of the planetary ball mill allows the slurry to evenly contact the inner surface of the gypsum mold. As the rotation time of the planetary ball mill increases, the gypsum mold continuously absorbs moisture. Finally, the ATZ slurry with uniform fineness inside the gypsum mold is completely and evenly adhered to the wall and solidified to form a hollow ATZ ceramic green ball; S4, removing the gypsum mold with the hollow ATZ ceramic green ball and drying it, because the two materials shrink differently and produce delamination, the hollow ATZ ceramic green ball falls off, and then disassembling the gypsum mold according to the disassembly method of the gypsum mold, and taking out the hollow ATZ ceramic green ball; S5. Take one of the hollow ATZ ceramic green balls from the same batch and knock it open to observe whether there is any slurry lump that has not been completely absorbed by the gypsum mold; if not, it is judged to be qualified; S6. The qualified batch of hollow ATZ ceramic green balls are sintered according to a certain normal pressure air atmosphere sintering system, and then polished according to a certain polishing method after sintering. The polished hollow ATZ ceramic green balls are sorted according to a certain sorting method to obtain the final qualified hollow ATZ ceramic balls for bearings.
2. The method for preparing a hollow ATZ ceramic ball for bearing according to claim 1, characterized in that: The empirical formula in step S1 is: Formula(1) Formula (2) Formula (3) Formula(4) ρ 空 : Density of hollow ATZ ceramic ball, unit: g / cm 3 ; ρ 实 : Theoretical or optimal sintering density of ATZ ceramic material, unit: g / cm 3 ; ρ 生坯层 : Density of the dense part of the hollow ATZ ceramic green ball after demolding after slip injection molding, unit: g / cm 3 ; ρ 水 : Density of pure water, unit: g / cm 3 ; D 外 : The outer diameter of the qualified hollow ATZ ceramic ball after final polishing, in mm; D 外生坯 : The outer diameter of the hollow ATZ ceramic green ball, that is, the inner diameter of the cavity of the gypsum mold, in mm; D 空生坯 : Hollow cavity diameter of hollow ATZ ceramic green ball, unit: mm; D 空 : The inner diameter of the qualified hollow ATZ ceramic ball after final polishing, in mm; K1: shrinkage ratio of hollow ATZ ceramic green balls after sintering; K2: moisture content of hollow ATZ ceramic green balls; K3: polishing compensation coefficient, unit: mm; SC: solid content of ATZ slurry to be prepared; The above four empirical formulas and related empirical constants can be used to calculate the solid content of the ATZ slurry and the spherical cavity size of the gypsum mold required for grouting of the hollow ATZ ceramic ball to be designed.
3. The method for preparing a hollow ATZ ceramic ball for bearing according to claim 1, characterized in that: In the step S2, the proportion of 3Y zirconium oxide in the ATZ powder is 80 parts by mass, and the proportion of aluminum oxide is 20 parts by mass.
4. The method for preparing a hollow ATZ ceramic ball for bearing according to claim 1, characterized in that: In the step S2, 0.3-0.5% of a dispersion stabilizer is added to the grinding ATZ slurry, and the dispersion stabilizer is CE64 or polyacrylic acid.
5. The method for preparing a hollow ATZ ceramic ball for bearing according to claim 1, characterized in that: The rotation speed of the planetary ball mill is 300-400r / min.
6. The method for preparing a hollow ATZ ceramic ball for bearing according to claim 1, characterized in that: In step S4, the drying temperature is between 30-40° C. and the drying time is 3-6 hours.
7. The method for preparing a hollow ATZ ceramic ball for bearing according to claim 1, characterized in that: In step S6, the normal pressure air atmosphere sintering system is as follows: the heating rate at 0-120°C is 1.5-2°C / min, the heating rate at 120-350°C is 0.4-0.6°C / min, the heating rate at 350-650°C is 0.3-0.5°C / min, the temperature is kept at 650-650°C for 120min, the heating rate at 650-1450°C is 1.0-1.2°C / min, the temperature is kept at 1450°C for 180min, and the cooling rate at 1450-1000°C is 1.5-2.0°C / min.
8. The method for preparing a hollow ATZ ceramic ball for bearing according to claim 1, characterized in that: In the step S6, a certain polishing method is: firstly perform rough polishing: add 60-70wt% of hollow ATZ beads, 20-25wt% of pure water, 4-5wt% of 20-50µm white corundum particles, and 0.5wt% of polyacrylic acid dispersant in a vertical sand mill; then perform fine polishing: add 50-60wt% of the hollow ATZ beads after rough polishing, 25-30wt% of pure water, and 6-8wt% of 1-5µm alumina powder in a vertical sand mill.
9. The method for preparing a hollow ATZ ceramic ball for bearing according to claim 1, characterized in that: In step S6, a certain sorting method is: firstly, a roughness detector is used to sort out the hollow ATZ ceramic balls with a roughness less than 0.05 μm as roughness qualified products; then a laser particle size analyzer is used to test the roundness of each hollow ATZ ceramic ball, and the hollow ATZ ceramic balls with a roundness greater than or equal to 99.9% are regarded as roundness qualified products; Then conduct density test, and select the hollow ATZ ceramic balls with density less than or equal to 3g / cm3 as qualified products; Then, quality classification is carried out, and the hollow ATZ ceramic balls with a mass deviation of less than 0.05g are placed in the same box for storage; the hollow ATZ ceramic balls with a mass difference of less than 0.05g are sorted according to size, and finally the hollow ATZ ceramic balls with a diameter error within the design size of ±0.05mm are sorted out as the final qualified products.
10. A hollow grouting gypsum mold, characterized in that: It includes a plug assembly, an upper mold convex assembly, a lower mold concave assembly and a lower mold concave-convex assembly. The upper mold convex assembly is spliced and assembled with the lower mold concave-concave assembly and the lower mold concave-convex assembly. After assembly, a spherical cavity is formed between the upper mold convex assembly, the lower mold concave-concave assembly and the lower mold concave-convex assembly. A slurry filling port is opened on the upper mold convex assembly to connect the spherical cavity, and the plug assembly is sealed on the slurry filling port.
Citation Information
Patent Citations
Preparation method of zirconium oxide hollow spheres
CN102584279A
Production device and method of multilayer ice ball
CN110030778A
Preparation method of oxide structure ceramic-based hollow floating ball
CN113979746A
Environment-friendly efficient ceramic product production equipment and use method
CN114179205A
Device and method for preparing seamless ceramic hollow floating ball
CN114905618A